Evaluation of potato (Solanum tuberosum L.) genotypes for resistance to late blight at Sinana Southeastern Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2016)
Late blight caused by Phytophthora infestans (Mont.) de Bary, is one of the most significant constraints to potato production in Bale high lands and other regions of Ethiopia. Hence, this requires to develop high yielding and late blight resistant varieties. Therefore, this study was conducted to determine host resistance of potato against Phytophthora infestans in order to develop late blight resistant/tolerant genotypes. The experiment was laid out in randomized complete block design with three replications at Sinana Agricultural Research Center during 2014 main cropping season. The genotypes showed highly significant (P